THE HERPETOFAUNA OF BOQUEIRÃO DA ONcA: AN IMPORTANT NATURAL HERITAGE SITE IN THE CAATINGA OF BRAZIL - Cavalheri, Diego Gomiero [UNESP]; Capela, Danilo Jose Vieira; Santana, Diego Jose; Mariotto, Lucas ferriolli; Mangia, Sarah (Herpetological Conservation & Biology, 2024)
The conservation units of Boqueirao da Onca, Brazil, a mosaic of protected areas located in the sub- middle of the Sao Francisco River, host the largest continuum of preserved Caatinga vegetation in the world. Although the region represents a biodiversity hotspot in the Caatinga domain, many relevant areas remain unsampled for amphibians and reptiles. To fill important knowledge gaps about the distribution, ecology, and diversity of herpetofauna from Caatinga, we present here a list of amphibian and reptile species of the Boqueirao da Onca, in Bahia state, northeastern Brazil. We conducted field expeditions between August 2019 and May 2021, totaling 64 sampling days using six sampling methods. We recorded 76 species, including 24 amphibians, one chelonian, 19 lizards, 27 snakes, and five amphisbaenians. This result represents the highest diversity reported in the Caatinga to date, compared to studies conducted in other locations throughout the domain. Additionally, we extended the geographic distribution of three species, and identified a frog and a lizard as potentially new species. The diversity of mammals, birds, and now amphibians and reptiles found in the area highlights the importance of Boqueirao da Onca as a priority area for conservation programs in the Caatinga domain.
Keywords: amphibians; conservation; inventory; reptiles; species richness